2020
DOI: 10.1016/j.joca.2020.02.831
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the dr. Bart application on healthcare use and clinical outcomes in people with osteoarthritis of the knee and/or hip in the Netherlands; a randomized controlled trial

Abstract: Objective: To evaluate the short-term effects of use of the dr. Bart app, compared to usual care, on the number of secondary health care consultations and clinical outcomes in people with knee/hip OA in the Netherlands. Method: A randomized controlled design involving participants !50 years with self-reported knee and/ or hip OA recruited from the community. The number of secondary health care consultations (primary outcome) and secondary outcomes were assessed at baseline, 3 and 6 months via online questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 50 publications
2
49
0
Order By: Relevance
“…A summary of the study information, participant characteristics and main findings of the 11 included studies is reported in Table 1 and briefly described. Six studies included individuals with knee OA [ 25 – 30 ], one included individuals with hip OA [ 31 ] and four included individuals with either hip or knee OA [ 15 , 32 34 ]. Ten studies reported a higher numbers of female participants (range, 56–100%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A summary of the study information, participant characteristics and main findings of the 11 included studies is reported in Table 1 and briefly described. Six studies included individuals with knee OA [ 25 – 30 ], one included individuals with hip OA [ 31 ] and four included individuals with either hip or knee OA [ 15 , 32 34 ]. Ten studies reported a higher numbers of female participants (range, 56–100%).…”
Section: Resultsmentioning
confidence: 99%
“…The sample size of the studies ranged from 40 to 427. Four studies included a follow-up at 12-months [ 15 , 26 , 31 , 34 ], one at 9 months [ 28 ] and the remaining six studies had no follow-up [ 25 , 27 , 29 , 30 , 32 , 33 ]. The control groups varied amongst included studies.…”
Section: Resultsmentioning
confidence: 99%
“…The original randomised controlled trial included 427 participants with knee/hip OA [ 14 ]. Of those, 214 participants were randomised into the intervention group and subsequently included in the current explorative study.…”
Section: Resultsmentioning
confidence: 99%
“…The content of the dr. Bart app is based on the Fogg model for behavioural change, augmented with reminders, rewards and self-monitoring to reinforce app engagement [ 13 , 23 ]. In a randomized evaluation, we found that the dr. Bart app did not impact health care utilisation (HCU), but resulted in small positive effects on pain, symptoms and activities of daily living [ 14 ]. However, a fundamental issue in eHealth research is non-usage attrition; a proportion of participants do not use the intervention at all, or use it sparsely [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…This letter is in response to the letter by Chudy et al 13 regarding our article: 'Effect of the dr. Bart application on health care use and clinical outcomes in people with osteoarthritis of the knee and/or hip in the Netherlands; a randomized controlled trial' 1 .…”
mentioning
confidence: 99%